The GBAP1 pseudogene acts as a ceRNA for the glucocerebrosidase gene GBA by sponging miR-22-3p. Issue 1 (December 2017) - Straniero, Letizia; Rimoldi, Valeria; Samarani, Maura; Goldwurm, Stefano; Di Fonzo, Alessio; Krüger, Rejko; Deleidi, Michela; Aureli, Massimo; Soldà, Giulia; Duga, Stefano; Asselta, Rosanna
Abstract Mutations in theGBA gene, encoding lysosomal glucocerebrosidase, represent the major predisposing factor for Parkinson's disease (PD), and modulation of the glucocerebrosidase activity is an emerging PD therapy. However, little is known about mechanisms regulatingGBA expression. We explored the existence of a regulatory network involvingGBA, its expressed pseudogeneGBAP1, and microRNAs. The high level of sequence identity betweenGBA andGBAP1 makes the pseudogene a promising competing-endogenous RNA (ceRNA), functioning as a microRNA sponge. After selecting microRNAs potentially targeting both transcripts, we demonstrated that miR-22-3p binds to and down-regulatesGBA andGBAP1, and decreases their endogenous mRNA levels up to 70%. Moreover, over-expression ofGBAP1 3′-untranslated region was able to sequester miR-22-3p, thus increasingGBA mRNA and glucocerebrosidase levels. The characterization ofGBAP1 splicing identified multiple out-of-frame isoforms down-regulated by the nonsense-mediated mRNA decay, suggesting thatGBAP1 levels and, accordingly, its ceRNA effect, are significantly modulated by this degradation process. Using skin-derived induced pluripotent stem cells of PD patients withGBA mutations and controls, we observed a significantGBA up-regulation during dopaminergic differentiation, paralleled by down-regulation of miR-22-3p. Our results describe the first microRNA controllingGBA and suggest that theGBAP1 non-coding RNA functions as aGBA ceRNA.